Advanced information systems engineering : CAiSE Forum 2020, Grenoble, France, June 8-12, 2020, Proceedings /: CAiSE Forum 2020, Grenoble, France, June 8-12, 2020, Proceedings. (2020) - Unknown
No abstract available